Batas Usia Perkawinan dalam Undang-Undang Keluarga Islam Negeri Selangor Tahun 2003: Analisis Perspektif Maqasid Al-Syari’ah (Marriage Age Limit in Selangor State Islamic Family Law 2003: Analysis of Maqasid Shari'a Perspective) - Munir, Badrul; Shafiq, Tengku Ahmad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2019)
Islam does not restrict age of marriage. But the state of Selangor Limited the age of 18 years for men and 16 years for women. According to maqashid sharia, an ideal age of marriage is an age capable of realizing The objectives of marriage sharia. In the discussion of this article, authors use primary and secondary data, the primary data obtained from the research library is research on Selangor Islamic Family Law in 2003, Quran, Hadith and several books of fikih. Secondary data is obtained from supporting sources of data that authors need then analyzed using qualitative descriptive methods. The results showed that there was a legal basis for establishing an age limit in marriage but only abstract and there is no evidence to increase the age of marriage. The reason of the Selangor State Legislative Assembly established an age limit in the Selangor Islamic Family Law of 2003 is in accordance with community needs in those days. But the law is no longer reasonable to practice with the state of Selangor society at present.